Collaborative inventory coordination model supported in a sociotechnical approach of systems - Palacio-León, Oscar; Barrios-León, Marianna; Adarme-Jaimes, Wilson (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2018)
This paper presents an alternative model of inventory coordination for vertical integration between a supplier and multiple customers. The originality of the model lies in three main elements. The first is that the level of service offered follows a deductive approach, using a priori a mathematical definite model. The second one is that the supplier directs the strategy of management of the availability of the collaborative inventory. The third one is that the methodological design uses a technical - economic validator. First, the literature checked to position the investigation. Later, they present the principal methodological elements that were used, principally the procedure to value the impact of the approach sociotécnico of systems load and improvement of the model ARU in that supports the scheme of collaboration. Finally, the validation results of the model are presented and analyzed in critical form.